Multiple tropical infections hepatitis, malaria, and leptospirosis induced acute kidney injury: a case report. - Kartik Goel; Shubhi Gupta; Ravi Bhargav; Shailesh Kumar; Rupesh Yadav (Critical Care Innovations)
In tropical regions, infections such as malaria, dengue, leptospirosis, scrub typhus, and viral hemorrhagic fevers frequently result in acute kidney injury (AKI). Pathogenesis involves direct damage by pathogens, immune-mediated injury, and systemic hemodynamic changes. We present the case of a 28-year-old male with no known comorbidities admitted with complaints of fever for the past 12 days, yellowish discolouration of sclera, vomiting, abdominal distension, dyspnea, and decrease in urine output. The patient recently travelled to West Bengal (tropical regions) before the symptom onset. The patient was tested positive for Hepatitis A, Plasmodium vivax, and Leptospira. The patient was treated with IV antibiotics (ceftriaxone and doxycycline for 5 days), including coverage for tropical infections such as leptospirosis and antimalarial (IV artesunate for 3 days). The patient had a decrease in urine output with worsening of KFT and fluid overload for which repeated hemodialysis was performed. Renal function did not show improvement. A renal biopsy was performed for persistent AKI. The biopsy was suggestive of acute tubule interstitial nephritis (ATIN) with plasma cell infiltration. The patient was further managed with Inj. Methylprednisolone 1 g and urine output gradually improved. After day 3 of the start of the steroid, the patient’s dyspnea, acidosis, and abdominal distention resolved. The patient was discharged with steroids (prednisolone 40 g with weekly re-straining). At follow-up, the patient was asymptomatic with his normal liver function tests (LFT) and kidney function tests (KFT). This case highlights the complexity of diagnosing and managing AKI induced by tropical fevers. The overlap of infections of malaria, leptospirosis, and hepatitis posed significant diagnostic challenges. Renal biopsy played a crucial role in identifying ATIN as the underlying pathology, guiding the use of immunosuppressive therapy. Early recognition and comprehensive management, including infection-specific treatments and supportive care, are vital to improving outcomes in patients with tropical fever-induced AKI.